Integrating Biotechnology, Physiology, and Agroecological Practices for Sustainable Crop Production and Protection - Yash Yadav (International Journal of Trends in Horticulture, 2025)
Global agriculture is currently confronting a wide range of complex challenges, including a rapidly growing population, climate change, increasing pest and disease pressures, soil degradation, water scarcity, and the urgent need for sustainable intensification of crop production. Addressing these issues requires integrated strategies that combine crop improvement (through modern breeding and biotechnology), precision agronomic practices related to soil, irrigation, and nutrition, as well as advancements in plant physiology, molecular biology, and holistic pest, disease, and weed management.This review explores recent developments across these interconnected disciplines. It highlights how modern plant breeding—encompassing genomics, gene editing, and hybridization—along with molecular biology and biotechnology, contributes to the development of crop varieties with higher yield potential, improved tolerance to abiotic stresses such as drought, salinity, and heat, and better resistance to pests and pathogens. The article also examines physiological and horticultural insights that support optimized plant growth under varying environmental conditions.Further, the review addresses advances in soil science, irrigation, nutrient management, crop modelling, and crop ecology, all of which enhance resource-use efficiency and environmental sustainability. In the domain of pest, disease, and weed management, innovations such as integrated pest management (IPM), biological control, biopesticides, targeted chemical strategies, and nano-formulations are discussed for their ability to reduce chemical inputs while maintaining or increasing yields. Disease management topics include molecular diagnostics, plant virology control strategies, and the development of pathogen-resistant genotypes. Weed management approaches using cultural practices, mechanical control, and bioherbicides are also considered.A dedicated section highlights entomology and insect pest dynamics, focusing on natural enemies, vector biology, and pest modelling. Soil health and irrigation strategies are presented as foundational pillars of sustainable crop production, covering conservation tillage, precision irrigation, manipulation of the soil microbiome, and nutrient cycling.The review further explores the interconnectedness of these components through crop ecology and modelling, which provide predictive insights into crop and pest responses under climate change scenarios and support informed decision-making. Finally, key bottlenecks are identified, including regulatory and biosafety challenges for biotechnology, public acceptance of GM and gene-edited crops, high costs and scalability issues of emerging technologies, knowledge gaps among farmers, and potential ecological risks.Overall, the article concludes that a systems-based approach—integrating breeding, biotechnology, physiology, agronomy, and comprehensive pest, disease, and weed management supported by modelling tools—offers the most effective pathway toward resilient, high-yielding, and environmentally sustainable agriculture.
Keywords: Crop Improvement; Sustainable agriculture; biotechnology; crop modelling; integrated pest management